Analysis of the text of the poem by Abai «Asempaz bolma arnege» in light of the Qur'an and Hadith (Journal of Oriental Studies, 2016)
This article provides an analysis of the poem Abai Kunanbaev, which begins with the words «Asempaz bolma arnege» in the light of religious texts. Thus the connection of ideas of the poet with a religious text.
Keywords: Abai; verse; hadith; Text